Prediction of Hearing Preservation in Vestibular Schwannoma Surgery According to Tumor Size and Anatomic Extension - Bozhkov, Yavor; Shawarba, Julia; Feulner, Julian; Winter, Fabian; Rampp, Stefan; Hoppe, Ulrich; Dörfler, Arnd; Iro, Heinrich; Buchfelder, Michael; Rössler, Karl (Otolaryngology-Head and Neck Surgery, 2021)
Objective: Vestibular schwannoma (VS) surgery is feasible for various tumor sizes that are inappropriate for wait and scan or radiosurgery. The predictive value of 2 grading systems was investigated for postoperative hearing preservation (HP) in a large series. Study Design: Retrospective analysis. Setting: Neurosurgical patient database of the University of Erlangen was queried between 2014 and 2017. Methods: Retrospective single-center analysis on 138 VSs operated on via a retrosigmoidal approach. The mean tumor size was 20.4 mm (SD, 7.6 mm) with fundal infiltration in 67.4%. The overall resection rate was 93.5%. Tumors were classified preoperatively by the 3-tier Erlangen grading system depending on size or the anatomically based 4-tier Koos grading system. Results: Preoperative hearing preservation was found in 70.3% of patients and was significantly correlated to tumor size (P =.001). For Erlangen grading, a mean postoperative serviceable hearing preservation rate of 32% was achieved: 83.3% for tumors <12 mm, 30.3% for tumors between 12 and 25 mm, and 5.3% for tumors >25 mm. In contrast, according to Koos grading, postoperative serviceable hearing preservation was 100% for grade 1 tumors (meatal), 35.6% for grade 2 (cisternal), 23.1% for grade 3 (brainstem contact), and 21.7% for grade 4 (brainstem compression). Of the total cohort, 86% had normal or nearly normal postoperative facial function (House-Brackmann grades 1 and 2). Conclusion: Surgery on small VSs can achieve excellent hearing preservation. Different grading has a significant influence on and correlates with postoperative hearing preservation. Tumor size seems more important than anatomic relationship.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Erlangen vestibula schwannoma grading; grading systems; hearing preservation; Koos vestibular schwannoma grading; vestibular schwannoma surgery